Sample-to-result molecular infectious disease assays: clinical implications, limitations and potential. (3rd March 2016) - Beal, Stacy G.; Assarzadegan, Naziheh; Rand, Kenneth H.
ABSTRACT: Molecular infectious disease diagnostic tests have undergone major advances in the past decade and will continue to rapidly evolve. Assays have become extraordinarily simple to perform, eliminating the need for pre-analytic sample preparation and post-amplification analysis. This allows these tests to be performed in settings without sophisticated expertise in molecular biology, including locations with limited resources. Additionally, the sensitivity and specificity of these assays is superb and many offer extremely fast turn-around times. These tests have major impacts on patient care, but also have some limitations.